2016
DOI: 10.1111/ijsa.12149
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Cultural Intelligence Scale in a Saudi Arabian Context

Abstract: The purpose of this study was to evaluate the psychometric properties of the cultural intelligence scale (CQS) in a Saudi Arabian context. The CQS was administered to a random sample of 553 undergraduate students at Hail University. Results of a confirmatory factor analysis (CFA) supported the four‐factor structure of the CQS: cognitive, metacognitive, motivational, and behavioral. In addition, the results of a second‐order CFA indicated that these four factors can be further collapsed into one general factor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…Also female students consistently presented higher behavioural CQ compared to their male counterparts. However, literature evidence is very uneven in this regard, and consequently the question as to why gender is a significant subcategory for behavioural CQ remains unanswered (Khodadady andGhahari (2011), Bücker andKorzilius (2015), Al-Dossary (2016), Brancu, Munteanu et al (2016), Kamal Abdien and Jacob (2019), Tu, Zhang et al (2020)). Further exploration into the CQS survey reveals that the items BEH1 I change my verbal behaviour (e.g., accent, tone) when a cross-cultural interaction requires it and BEH4 I change my nonverbal behaviour when a cross-cultural situation requires it stand for the largest and smallest difference in the behavioural intelligence dimension, respectively, between males and females.…”
Section: Resultsmentioning
confidence: 99%
“…Also female students consistently presented higher behavioural CQ compared to their male counterparts. However, literature evidence is very uneven in this regard, and consequently the question as to why gender is a significant subcategory for behavioural CQ remains unanswered (Khodadady andGhahari (2011), Bücker andKorzilius (2015), Al-Dossary (2016), Brancu, Munteanu et al (2016), Kamal Abdien and Jacob (2019), Tu, Zhang et al (2020)). Further exploration into the CQS survey reveals that the items BEH1 I change my verbal behaviour (e.g., accent, tone) when a cross-cultural interaction requires it and BEH4 I change my nonverbal behaviour when a cross-cultural situation requires it stand for the largest and smallest difference in the behavioural intelligence dimension, respectively, between males and females.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the CQS has strong construct validity (Matsumoto & Hwang, 2013). Convergent and discriminative validity for the CQS was assessed using average variance extraction (AL-Dossary, 2016;Moyano et al, 2015). The results observed that motivational CQ (mean = 0.51) and metacognition CQ (mean = 0.51) demonstrated adequate convergent validity, while cognitive and behavioral CQ were slightly lower.…”
Section: Measurementioning
confidence: 99%
“…While international students studying in the United States are required to hold an adequate English proficiency level, the validity of the CQS assessment in a foreign language is unknown. Several studies have investigated the usefulness of the CQS assessment in multiple languages (AL-Dossary, 2016;Moyano et al, 2015); however, it is unknown if the CQS scores would differ in international students at US universities based on the language of the questionnaire.…”
Section: Limitations Strengths and Future Researchmentioning
confidence: 99%
“…However, as Sinangil and Ones (2001, p. 433) pointed out, expatriate adjustment 'is not an end in itself, but rather a part of a process that allows the expatriate to be able to focus on and carry through the tasks of the job that he/she has been sent to perform.' In fact, CCA is an immediate determinant of performance (e.g., Bhaskar-Shrinivas, Harrison, Shaffer, & Luk, 2005;Black, 1990;Selmer, 2006a) and it is closely related to cultural intelligence (Al-Dossary, 2016).…”
Section: Definitional Issues Of Expatriate Effectivenessmentioning
confidence: 99%
“…The third aspect included in the conceptualization of expatriate effectiveness is CCA, and it was probably the criterion most frequently used in expatriate research (Caligiuri et al, ; Sinangil & Ones, ). However, as Sinangil and Ones (, p. 433) pointed out, expatriate adjustment ‘is not an end in itself, but rather a part of a process that allows the expatriate to be able to focus on and carry through the tasks of the job that he/she has been sent to perform.’ In fact, CCA is an immediate determinant of performance (e.g., Bhaskar‐Shrinivas, Harrison, Shaffer, & Luk, ; Black, ; Selmer, ) and it is closely related to cultural intelligence (Al‐Dossary, ).…”
Section: Introductionmentioning
confidence: 99%